PEMERIKSAAN PROFIL LIPID PADA JEMAAT LANSIA SALAH SATU GEREJA KRISTEN DI YOGYAKARTA - Patramurti, Christine; Triwulandari, Erna; Nastiti, Christofori Maria Ratna Rini (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Lipid profile examination including total cholesterol level, triglycerides level and high-density lipoprotein cholesterol reduction is essential to be done as a routine activity quinquennially to prevent someone from the risk of cardiovascular diseases, diabetes and obesity. This kind of examination is mandatory for the elderly people to maintain their quality of life. In order to support the government program on the prevention of the cardiovascular diseases, a team of social service of Faculty of Pharmacy Universitas Sanata Dharma (FFUSD) was organizing an event of lipid profile examination in one of Christian church located in Kalasan, Yogyakarta. As many as 35 elderly people were enthusiastically participating on the event. A nurse from Poliklinik Sanata Dharma was appointed to take the blood samples, which were further taken to the Biochemistry Laboratory in FFUSD to get analysed. The results were sent to the participants in private. The overall blood lipid profiles of most participants showed good level of quality, indicating that they have been trying to manage their life healthily. However, as much as 62. 8% of participants showed a low level of the high-density lipoprotein cholesterol.  This was believed due to the food intake which was still rich in oil and fat.  The event was very succesful and the responses were very positive. The participants felt assisted with a fast and accurate results sent.